2014
DOI: 10.1038/leu.2014.267
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and biologic significance of DNMT3B expression in older patients with cytogenetically normal primary acute myeloid leukemia

Abstract: DNMT3B encodes a DNA methyltransferase implicated in aberrant epigenetic changes contributing to leukemogenesis. We tested whether DNMT3B expression, measured by NanoString nCounter assay, associates with outcome, gene- and microRNA-expression and DNA methylation profiles in 210 older (≥60 years) adults with primary, cytogenetically normal AML (CN-AML). Patients were dichotomized into high versus low expressers using median cut. Outcomes were assessed in the context of known CN-AML prognosticators. Gene- and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
53
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 58 publications
8
53
1
Order By: Relevance
“…Whereas recent studies have reported that clinical outcome of older patients with CN-AML is influenced by several recurrent mutations, patients with apparently identical cytogenetic and molecular "makeup" do not have uniform outcomes (11)(12)(13)(14)(15)(16)(17)(18)(19). This may result from additional undiscovered genetic alterations, which may identify smaller, clinically meaningful patient groups for which it is possible to identify specific therapeutic targets.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Whereas recent studies have reported that clinical outcome of older patients with CN-AML is influenced by several recurrent mutations, patients with apparently identical cytogenetic and molecular "makeup" do not have uniform outcomes (11)(12)(13)(14)(15)(16)(17)(18)(19). This may result from additional undiscovered genetic alterations, which may identify smaller, clinically meaningful patient groups for which it is possible to identify specific therapeutic targets.…”
Section: Discussionmentioning
confidence: 82%
“…Our group reported that nucleophosmin (nucleolar phosphoprotein B23, numatrin) (NPM1) mutations are associated with a more favorable outcome in older patients with CN-AML (11), whereas fms-related tyrosine kinase 3 (FLT3) internal tandem duplications (FLT3-ITDs) and mutations in the additional sex combs like transcriptional regulator 1 (ASXL1), runt-related transcription factor 1 (RUNX1) and DNA (cytosine-5-)-methyltransferase 3 alpha (DNMT3A), which affect arginine codon 882 (R882-DNMT3A), are independently associated with worse disease-free survival (DFS) and OS (12)(13)(14)(15). We further showed that high expression levels of the brain and acute leukemia, cytoplasmic (BAALC), v-ets avian erythroblastosis virus E26 oncogene homolog (ERG), meningioma (disrupted in balanced translocation) 1 (MN1), and DNA (cytosine-5-)-methyltransferase 3 beta (DNMT3B) genes are associated with unfavorable outcome in older patients with CN-AML (16)(17)(18).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Niederwieser et al (17) reported that high expression levels of DNA (cytosine-5-)-methyltransferase 3β were associated with differentially expressed miR-133b in older adults with primary, cytogenetically normal acute myeloid leukemia. Therefore, the present study hypothesized that epigenetic factors may contribute to the downregulation of miR-133b, although this requires further investigation in future studies.…”
Section: A B C D Discussionmentioning
confidence: 99%